2020
DOI: 10.1038/s41598-020-62377-1
|View full text |Cite
|
Sign up to set email alerts
|

A live-cell super-resolution technique demonstrated by imaging germinosomes in wild-type bacterial spores

Abstract: Time-lapse fluorescence imaging of live cells at super-resolution remains a challenge, especially when the photon budget is limited. Current super-resolution techniques require either the use of special exogenous probes, high illumination doses or multiple image acquisitions with post-processing or combinations of the aforementioned. Here, we describe a new approach by combining annular illumination with rescan confocal microscopy. This optics-only technique generates images in a single scan, thereby avoiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…In our study, the primary objective was to ascertain whether the GerRB-SGFP2 fusion protein can be visualized and localized in B. cereus dormant spores, and our work showed that what is almost certainly a germinosome can be visualized by its GerRB-SGFP2 fluorescence in almost a third of B. cereus spores ( Figure 2 H). However, the ~30% of B. cereus spores exhibiting a germinosome was much lower than that for germinosomes in B. subtilis spores [ 25 , 26 , 29 ]. Reasons for this large difference in apparent levels of germinosomes are not clear, but there are a number of possibilities including the following.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the primary objective was to ascertain whether the GerRB-SGFP2 fusion protein can be visualized and localized in B. cereus dormant spores, and our work showed that what is almost certainly a germinosome can be visualized by its GerRB-SGFP2 fluorescence in almost a third of B. cereus spores ( Figure 2 H). However, the ~30% of B. cereus spores exhibiting a germinosome was much lower than that for germinosomes in B. subtilis spores [ 25 , 26 , 29 ]. Reasons for this large difference in apparent levels of germinosomes are not clear, but there are a number of possibilities including the following.…”
Section: Discussionmentioning
confidence: 99%
“…In B. subtilis spores, GRs are localized in 1-3 IM foci, termed a germinosome, for which GerD acts as a scaffold for GR assembly [21,24]. Recent work by our laboratory, using super-resolution three-dimensional structured illumination microscopy (3D-SIM) as well as annular Rescan Confocal Microscopy has allowed us to quantify germinosomes in single spores as well as to monitor germinosome dynamics upon germinant addition to wild-type B. subtilis spores [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The germinosome comprises germination receptors, scaffolding proteins and other components, such as the SpoVA protein involved in DPA transport ( Griffiths et al, 2011 ). Fluorescence visualization studies reveal that the germinosome localizes at one pole of the dormant endospore, then disperses as germination progresses ( Troiano et al, 2015 ; Breedijk et al, 2020 ; Wang et al, 2020 ). The germination cascade is then followed by degradation of the spore cell wall by lytic enzymes, increasing permeability and allowing Ca 2+ -DPA complexes and ions to escape the endospore in order to be replaced with water from the environment ( Griffiths et al, 2011 ; Wang et al, 2015 ).…”
Section: Germinationmentioning
confidence: 99%
“…They call the method rescan confocal microscopy. Breedijk et al proposed using annular illumination to improve the transverse resolution [61].…”
Section: Combining Patterned Illumination With Imaging Using Detected Lightmentioning
confidence: 99%